Thickness and Diameter in Melanoma: Is There a Relation?. Issue 1 (January 2016) - Crocetti, Emanuele; Fancelli, Laura; Caldarella, Adele; Buzzoni, Carlotta
Objective: To evaluate the relationship between diameter and Breslow's thickness in skin melanoma. Methods: 2, 071 skin melanomas incident in the area of activity of the Tuscany Cancer Registry (central Italy) were analyzed. Pearson's linear correlation coefficient r was computed between diameter and Breslow's thickness. Results: There was a statistically significant, but rather small, correlation between diameter and Breslow (r = 0.39). The same was true for men and women, for older and younger patients, and for skin subsites. 22.3% of the examined skin melanomas had a diameter ≤6 mm. Conclusions: There was a statistically significant, but small, correlation between Breslow's thickness and diameter in skin melanomas. Moreover, a non-negligible proportion of small lesions were thick and/or nodular.